Revisión Bibliográfica de los Protocolos de Manejo de Biocontroladores (Avispas sp.) en su Captura, Aislamiento y Propagación, Salache - Ceypsa 2021 - Jimenez Sagbay, Mishel Alexandra (2021)
Wasps are flying insects belonging to the Hymenoptera species, they are in a prominent place both for their beneficial actions as pollinating agents and insect-pest predators. The lack of insight into the important role that the wasp plays in the ecosystem is one reason why they are little known. Thus, the main objective of this work is to carry out a bibliographic review of the protocols for the capture, isolation and propagation of Wasps for their use as bio controllers. The methodology used in this research was based mainly on the problem´s identification, information search, bibliographic management, cleaning, coding of the database and systematization of the information collected from the last 10 years (2010-2021). It was found 64 documents of 150 inserted into the database that refer to the main methods of capturing Wasps that are entomological net, Malaise Traps type Townes, active traps, interceptor traps, sieve cages, McPhail Traps, focusing on the capture of adults. For the isolation methods 14 documents that give the procedure to the life cycle of the insect, the use of rearing chambers with their respective temperature and relative humidity to ensure the development of parasitoid eggs by the host. The propagation methods in 20 documents where the adaptation methodology that the Wasp fulfills for its oviposition of the females in the host is explained.